Final-Offer-Selection VS Last-Offer-by-Issue. Systems of Arbitration - Subbarao, A. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1978)
This paper analyzes both theoretically and empirically the impact of the two "one-or-the-other" Systems of binding interest arbitration on negociation process and outcome.